STUDI KASUS: KANGAROO FATHER CARE (KFC) DALAM ASUHAN KEBIDANAN PADA BAYI DENGAN BERAT BADAN LAHIR RENDAH (BBLR) - Kasmiati, Kasmiati; Fauziah, Arvicha (Poltekkes Kemenkes Maluku, 2023)
The incidence of newborns with low birth weight (LBW) in the world every year occurs in 20 million births, it is estimated that 15-20% of babies are born with LBW. Indonesia has a mortality rate for LBW newborns of 29%. The case study aims to determine the results of managing LBW newborns using the Kangaroo Father Care (KFC) method. The case study was carried out in the perinatology room at dr. P.P Maggretty Saumlaki Hospital, the method used was a case study approach for babies. Mrs. K.K with LBW for 4 days every 08.00-11.50 WIT with the application of the Kangaroo Father Care (KFC) method with management results where the heart rate increased, respiration was normal, body temperature was stable, there was an increase in body weight of 30 grams, a loving relationship was established between father and babies, and increasing fathers' knowledge in caring for their LBW babies. The conclusion is that the application of Kangaroo Father Care (KFC) positively effects on babies who experience LBW.